Respostas
respondido por:
2
7x^2-2x=0
delta=b^2-4ac
delta=(-2)^2-4.7.0
delta=4-0
delta=4
x=-b-/+ raiz de delta/2a
x=-(-2)-2/2.7
x=2-2/14
x=0/14
x=0
x=-(-2)+2/2.7
x=2+2/14
x=4/14 (:2)
x=2/7
delta=b^2-4ac
delta=(-2)^2-4.7.0
delta=4-0
delta=4
x=-b-/+ raiz de delta/2a
x=-(-2)-2/2.7
x=2-2/14
x=0/14
x=0
x=-(-2)+2/2.7
x=2+2/14
x=4/14 (:2)
x=2/7
respondido por:
2
7x²-2x=0
a=7
b=-2
c=0
Δ=b²-4.a.c
Δ=(-2)²-4.7.0
Δ=4-0
Δ=4
x=-b+-√Δ/2.a
x=-(-2)+-√4/2.7
x=4+2/7 = 6/7 e
x=4-2/7 = 2/7 portanto S=( 2/7 e 6/7)
a=7
b=-2
c=0
Δ=b²-4.a.c
Δ=(-2)²-4.7.0
Δ=4-0
Δ=4
x=-b+-√Δ/2.a
x=-(-2)+-√4/2.7
x=4+2/7 = 6/7 e
x=4-2/7 = 2/7 portanto S=( 2/7 e 6/7)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás